THE IMPORTANCE OF AI IN TEACHING ENGLISH - Kaljanova Gulmira Barlikbay qizi; Normatova Yulduz Nurnazarovna (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
Artificial Intelligence (AI) has rapidly transformed educational practices, particularly in the field of English language teaching (ELT). This paper explores the role of AI in enhancing language learning through personalized instruction, automated assessment, intelligent tutoring systems, and immersive learning environments. AI-powered tools such as chatbots, adaptive learning platforms, speech recognition software, and automated feedback systems support learners in developing reading, writing, listening, and speaking skills more efficiently. The study highlights how AI promotes learner autonomy, inclusivity, and teacher support while addressing challenges such as data privacy, ethical concerns, and teacher training. Using a qualitative review methodology, this paper analyzes recent scholarly literature to evaluate the effectiveness of AI-driven technologies in ELT. The findings suggest that AI, when integrated thoughtfully, can significantly improve learning outcomes and teaching effectiveness while redefining the role of English language teachers in the digital age.